2013
DOI: 10.1186/1471-2407-13-535
|View full text |Cite
|
Sign up to set email alerts
|

Altered features and increased chemosensitivity of human breast cancer cells mediated by adipose tissue-derived mesenchymal stromal cells

Abstract: BackgroundMesenchymal stromal cells (MSCs) represent heterogeneous cell population suitable for cell therapies in regenerative medicine. MSCs can also substantially affect tumor biology due to their ability to be recruited to the tumor stroma and interact with malignant cells via direct contacts and paracrine signaling. The aim of our study was to characterize molecular changes dictated by adipose tissue-derived mesenchymal stromal cells (AT-MSCs) and the effects on drug responses in human breast cancer cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 56 publications
4
71
0
1
Order By: Relevance
“…Furthermore, these findings are substantiated by a previous work demonstrating enhanced tumor cell growth by MSC [34][35][36][37], although there are also controversial studies suggesting a reduced tumor cell proliferation in the presence of MSC [38,39]. The divergent effects of MSC on tumor cells may be caused, in part, by a different activation status within the heterogeneous MSC population involving interference with the b-catenin pathway such as DKK-1-mediated depression of Wnt signaling [40].…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, these findings are substantiated by a previous work demonstrating enhanced tumor cell growth by MSC [34][35][36][37], although there are also controversial studies suggesting a reduced tumor cell proliferation in the presence of MSC [38,39]. The divergent effects of MSC on tumor cells may be caused, in part, by a different activation status within the heterogeneous MSC population involving interference with the b-catenin pathway such as DKK-1-mediated depression of Wnt signaling [40].…”
Section: Discussionsupporting
confidence: 57%
“…In our co-culture, stromal cells from liver and adipose also supported the proliferation of K562 cells. Recent reports have demonstrated that adipose tissue and associated stroma can maintain breast cancer cells and induce pharmacological resistance [34,35]. Additionally, the links between adipose tissue and activation of inflammation and chemokine pathways with regard to oncogenesis is becoming more recognized [36].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, major attention has been focused in order to clarify if the transfer of ASCs-containing SVF may increase the risk of breast cancer development or relapse [14]. Tumor microenvironment consists in a complex signaling network which influences the behavior of both resident stem cells and tumor cells [15]. Angiogenesis is one of the crucial events for cancer development and growth, and VEGF secretion plays a pivotal role in this process, thereby becoming a main target for antitumor strategies [16,17].…”
Section: Adipose Derived Stem Cells and Breast Cancer Progressionmentioning
confidence: 99%